2016
DOI: 10.1002/ange.201606381
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Pathway for the Preparation of Aryl(isoquinoline)iodonium(III) Salts and Synthesis of Radiofluorinated Isoquinolines

Abstract: Iodonium compounds playap ivotal role in 18 Ffluorination of radiopharmaceuticals containing non-activated arenes.H owever,p reparation of these species is limited to oxidation conditions or exchange with organometallics that are prepared from aryl halides.H erein we describe an ovel "onepot" process to assemble aryl(isoquinoline)iodoniums alts in 40-94 %y ields from mesoionic carbene silver complex and Aryl-I-Py 2 (OTf) 2 .T he method is general, practical, and compatible with well-functionalized molecules as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Of further note is an efficient 1‐pot pathway developed for the preparation of aryl(substituted‐isoquinolinyl)iodonium triflates based on treating mesoionic carbene silver complexes with the hypervalent iodine reagent, PhI(Py′) 2 (OTf) 2 where Py′ is a substituted pyridine (Figure ) . The method displayed tolerance for a wide variety of substituents (eg, alkyl, aryl, halogen, OMe, and ester) and gave 40% to 94%.yields.…”
Section: Discussionmentioning
confidence: 99%
“…Of further note is an efficient 1‐pot pathway developed for the preparation of aryl(substituted‐isoquinolinyl)iodonium triflates based on treating mesoionic carbene silver complexes with the hypervalent iodine reagent, PhI(Py′) 2 (OTf) 2 where Py′ is a substituted pyridine (Figure ) . The method displayed tolerance for a wide variety of substituents (eg, alkyl, aryl, halogen, OMe, and ester) and gave 40% to 94%.yields.…”
Section: Discussionmentioning
confidence: 99%
“…MeCN) to facilitate ion exchange between OTfa nd 18 F. After solvent removal, anonpolar medium (e.g. [129] Radiofluorination of ab road range of aryl(isoquinoline)iodonium salts was achieved with [ 18 F]Et 4 NF in 25-65 %RCY.Asproof of concept, a 18 F-labeled natural product, [ 18 F]fluoroaspergillitine, was achieved in 10 %R CY with am olar activity of 37 GBq mmol À1 . [127] In contrast to the "ortho effect", 18 Angewandte Chemie Reviews C(sp 2 )r eductive elimination occurred on the counterpart of the steric bulky mesityl group to allow access to av ariety of electron-rich, -neutral, and -deficient 18 F-arenes.Recently,the same authors improved their method through the formation of electron-rich mesityl(aryl)iodonium salts in situ, which offers apotential solution to synthesize electron-rich arylÀ 18 F bonds without the need for isolation with certain unstable electron-rich diaryliodonium salts.…”
Section: F-fluorination Of Hypervalent Iodine(iii) Compoundsmentioning
confidence: 99%
“…These iodonium compounds play an important role in 18 F-fluorination of radiopharmaceuticals containing non-activated arenes (Scheme 17). [54] Zhao et al reported an Ag-catalyzed sequential imination-annulation of 2-alkynyl aldehydes 6 with ammonium bicarbonate 39 as source of nitrogen donor to access isoquinolines. The generalized protocol was applied on various 2-alkynyl aldehydes bearing EDG and EWG (Scheme 18).…”
Section: Ag-catalyzed Isoquinoline Synthesismentioning
confidence: 99%
“…These iodonium compounds play an important role in 18 F‐fluorination of radiopharmaceuticals containing non‐activated arenes (Scheme 17). [54] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 99%